PEMANFAATAN BARANG MILIK DAERAH DAN PENGARUHNYA TERHADAP PENDAPATAN ASLI DAERAH (Studi Kasus Pada Pemerintah Kabupaten Timor Tengah Selatan) - Annisa Syafitrah Sakeh; Nur Diana; M. Cholid Mawardi (Universitas Islam Malang, 2022)
This study aims to obtain an overview of the effect of the Utilization of the Regional Property of South Central Timor Regency on the Regional Original Income of South Central Timor Regency. This research was conducted at the Regional Financial and Asset Management Agency of South Central Timor Regency. This type of research is descriptive and quantitative, where the subject under study is the Regional Regulation on Accountability of the Regional Revenue and Expenditure Budget and the Report on the Realization of the Regional Revenue of the South Central Timor Regency using documentation techniques. The results showed that: a). Realization of Regional Revenue, Regional Original Revenue, and Utilization of Regional Property of the South Central Timor Regency always does not meet the predetermined target. b). The ability to obtain levies on the use of regional assets in Timor Tengah Selatan Regency is relatively low, namely below 1%. c). Analysis of Trends in Ability to Obtain RPKD for South Central Timor Regency for the 2016-2020 period fluctuates every year. d). The contribution of the RPKD to the Regional Original Revenue of the Timor Tengah Selatan Regency is still below 5%. e). Trend Analysis of the Contribution of the RPKD to Regional Original Income in South Central Timor fluctuated during the 2016-2020 period. f). The influence of the use of the regional property on the original regional income of Timor Tengah Selatan Regency is relatively low.Keywords: Utilization of Regional Property, Regional Original Income